The Effect of Exercise Intervention on Disability and Kinesiophobia in a Retired Athlete With Old Patella Fracture: A Case Report - Su, Yuqin; Huang, Li; Liu, Haowei; Chen, Shifan; Peng, Li (Frontiers in Psychology, 2021)
Objectives: To evaluate the effect of exercise intervention on disability, pain and kinesiophobia in patients with chronic knee pain. Methods: A 33-year-old retired football player with chronic knee pain conducted the exercise intervention for 12 weeks, 1 h each time, three times a week. the retired football player completed the Lysholm Knee Score (LKS), Visual Analog Scale(VAS)，and the Tampa Scale for Kinesiophobia（TSK）were measured at pre-intervention, mid-intervention, and post-intervention. Results: Based on the functional training perspective, the patient were subjected to two stages of exercise intervention for a total of 12 weeks. The patient’s LKS score increased from 76 to 90, and the pain level of various physical states was relieved. When walking, the VAS score was reduced from 4 to 1, and when running, the VAS score was reduced from 5 to 2. Jumping VAS score for actions was reduced from 6 to 2, and the VAS score for of daily life activities was reduced from 3 points to 1. The patient’s TSK score from50 to 34. Conclusion: A 12-week exercise intervention could improve knee joint function, relieve pain and relieve Kinesiophobia.